Review of yeast culture concerning the interactions between gut microbiota and young ruminant animals - Liu, Shixiong; Yang, Lan; Zhang, Yufei; Chen, Hui; Li, Xueqiang; Xu, Zixuan; Du, Rui; Li, Xiao; Ma, Jiabin; Liu, Dacheng (Frontiers in Veterinary Science, 2024)
Microorganisms inhabit the gastrointestinal tract of ruminants and regulate body metabolism by maintaining intestinal health. The state of gastrointestinal health is influenced not only by the macro-level factors of optimal development and the physiological structure integrity but also by the delicate equilibrium between the intestinal flora and immune status at the micro-level. Abrupt weaning in young ruminants causes incomplete development of the intestinal tract resulting in an unstable and unformed microbiota. Abrupt weaning also induced damages to the microecological homeostasis of the intestinal tract, resulting in the intestinal infections and diseases, such as diarrhea. Recently, nutritional and functional yeast culture has been researched to tackle these problems. Herein, we summarized current known interactions between intestinal microorganisms and the body of young ruminants, then we discussed the regulatory effects of using yeast culture as a feed supplement. Yeast culture is a microecological preparation that contains yeast, enriched with yeast metabolites and other nutrient-active components, including β-glucan, mannan, digestive enzymes, amino acids, minerals, vitamins, and some other unknown growth factors. It stimulates the proliferation of intestinal mucosal epithelial cells and the reproduction of intestinal microorganisms by providing special nutrient substrates to support the intestinal function. Additionally, the β-glucan and mannan effectively stimulate intestinal mucosal immunity, promote immune response, activate macrophages, and increase acid phosphatase levels, thereby improving the body’s resistance to several disease. The incorporation of yeast culture into young ruminants’ diet significantly alleviated the damage caused by weaning stress to the gastrointestinal tract which also acts an effective strategy to promote the balance of intestinal flora, development of intestinal tissue, and establishment of mucosal immune system. Our review provides a theoretical basis for the application of yeast culture in the diet of young ruminants.